Development and Psychometric Properties of the DASS-Youth (DASS-Y): An Extension of the Depression Anxiety Stress Scales (DASS) to Adolescents and Children - Szabo, Marianna; Lovibond, Peter F. (Frontiers in Psychology, 2022)
The Depression Anxiety Stress Scales (DASS; Lovibond & Lovibond, 1995b) is a set of psychometrically sound scales that is widely used to assess negative emotional states in adults. In this project, we developed the Depression Anxiety Stress Scales for Youth (DASS-Y) and tested its psychometric properties. Data were collected from 2121 Australian children and adolescents aged 7-18 (61% female). This sample was split randomly into a calibration group (n = 1075, 61% female) and a cross-validation group (n = 1046, 60% female). First, we used Confirmatory Factor Analysis on the calibration group to test the 3-factor DASS model on 40 items we had developed in previous exploratory studies. We then selected the best-performing 21 items based on both statistical and theoretical considerations, guided by the structure and item content of the adult DASS. We cross-validated this new 21-item model in the second half of the sample. Results indicated good fit for the final 21-item 3-factor DASS model in both groups of children and adolescents. Multiple regression analyses showed that when scores on the other DASS-Y scales were held constant, the DASS-Y Depression scale had a strong negative relationship with positive affect and life satisfaction, the DASS-Y Anxiety scale was strongly associated with physiological hyperarousal, and the DASS-Y Stress scale was associated with excessive worrying. However, the relationship between Stress and worrying was only evident from age 10 onwards. Our results show that the core symptoms that define depression, anxiety and stress in children and adolescents are similar to those previously found in adults. The DASS-Y is a public domain instrument that we hope will prove useful in both research and clinical contexts.